2018
DOI: 10.3889/oamjms.2018.486
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs1042522 SNP with Clinicopathologic Factors of Breast Cancer Patients in the Markazi Province of Iran

Abstract: BACKGROUND:The nucleotide changes in different genetic loci increased the incidence risk of breast cancer.AIM:The aim of present study was to investigate genotype distribution at codon 72 of the TP53 gene (rs1042522) in breast cancer patients to achieve a potential diagnostic marker related to some demographic feathers.METHODS:In our case-control study, blood samples were collected from a total of 34 patients harboured breast cancer. DNA was extracted, and nested-PCR was performed. Products were digested with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
6
1
Order By: Relevance
“…Several studies reported that rs1042522 may play a significant role in BC development. However, studies have revealed controversial results regarding relationship between polymorphism genotypes and BC [22,23]. In our study, this polymorphism did not show any significant associations with studied BC characteristics and patient survival.…”
Section: Discussioncontrasting
confidence: 71%
“…Several studies reported that rs1042522 may play a significant role in BC development. However, studies have revealed controversial results regarding relationship between polymorphism genotypes and BC [22,23]. In our study, this polymorphism did not show any significant associations with studied BC characteristics and patient survival.…”
Section: Discussioncontrasting
confidence: 71%
“…However, no signi cant associations were found in the BMI < 18.5 kg/m 2 group. With a trend the same as tSNP rs12951053, one study has shown that SNP rs1042522 in TP53 may be associated with susceptibility to breast cancer among Iranian women with high BMI 14 .…”
Section: Discussionmentioning
confidence: 98%
“…With a trend the same as tSNP rs12951053, one study has shown that SNP rs1042522 in TP53 may be associated with susceptibility to breast cancer among Iranian women with high BMI. 14 …”
Section: Discussionmentioning
confidence: 99%